The zooxanthellate scleractinian coral Oulastrea crispata (Lamarck, 1816), an overlooked newcomer in the Mediterranean Sea? - MARIANI, SIMONE; OCAÑA VICENTE, OSCAR; LÓPEZ-SENDINO, PAULA; GARCÍA, MARÍA; RICART, AURORA MARTÍNEZ; GARRABOU, JOAQUIM; BALLESTEROS, ENRIC (Mediterranean Marine Science, 2018)
The zooxanthellate scleractinian coral Oulastrea crispata, a widely distributed species across central Indo-Pacific nearshore marine habitats, has been first reported from the Mediterranean Sea (Corsica) in 2014. Here we report on two new sites for this species in the NW Mediterranean Sea and provide a general description of external morphological characters of the colonies and a detailed account of the cnidom to help future identifications. Living specimens may appear virtually identical to small colonies (~5 cm) of the Mediterranean zooxanthellate scleractinian Cladocora caespitosa. While this species shows long, ramified, independent corallites, with cylindrical calices, O. crispata has enlarged, cup-like calices, which can be joined by the coenosteum. It also shows clear differences among several groups of nematocysts, principally the presence in the filaments of large penicilli (p-mastigophore) of one type, which are absent in C. caespitosa. Identifications based on underwater observations or even the analysis of photographs may easily lead to misleading identifications. We hypothesize that O. crispata may have gone unnoticed because of misidentifications as C. caespitosa. More detailed research is needed to get reliable maps of the actual distribution of this apparently non-indigenous species in the Mediterranean Sea.